The T6SSs of Pseudomonas aeruginosa Strain PAO1 and Their Effectors: Beyond Bacterial-Cell Targeting - Sana, Thibault G.; Berni, Benjamin; Bleves, Sophie (Frontiers in Cellular and Infection Microbiology, 2016)
Pseudomonas aeruginosa is an opportunistic pathogen responsible for many diseases such as chronic lung colonization in cystic fibrosis patients and acute infections in hospitals. The capacity of P. aeruginosa to be pathogenic towards several hosts is notably due to different secretion systems. Amongst them, P. aeruginosa encodes three Type Six Secretion Systems (T6SS), named H1- to H3-T6SS, that act against either prokaryotes and/or eukaryotic cells. They are independent from each other and inject diverse toxins that interact with different components in the host cell. Here we summarize the roles of these T6SSs in the PAO1 strain, as well as the toxins injected and their targets. While H1-T6SS is only involved in antiprokaryotic activity through at least seven different toxins, H2-T6SS and H3-T6SS are also able to target prokaryotic as well as eukaryotic cells. Moreover, recent studies proposed that H2- and H3-T6SS have a role in epithelial cells invasion by injecting at least three different toxins. The diversity of T6SS effectors is astounding and other effectors still remain to be discovered. In this review, we present a table with other putative P. aeruginosa strain PAO1 T6SS-dependent effectors. Altogether, the T6SSs of P. aeruginosa are important systems that help fight other bacteria for their ecological niche, and are important in the pathogenicity process.